Adjunctive 5-Hydroxytryptophan Slow-Release for Treatment-Resistant Depression: Clinical and Preclinical Rationale. (November 2016) - Jacobsen, Jacob P.R.; Krystal, Andrew D.; Krishnan, K. Ranga R.; Caron, Marc G.
Abstract : Serotonin transporter (SERT) inhibitors treat depression by elevating brain extracellular 5-hydroxytryptamine (5-HTExt ). However, only one-third of patients respond adequately. Treatment-resistant depression (TRD) is a major unmet need. Interestingly, elevating 5-HTExt beyond what is achieved by a SERT inhibitor appears to treat TRD. Adjunctive administration of 5-hydroxytryptophan (5-HTP) safely elevates 5-HTExt beyond the SERT inhibitor effect in humans; however, 5-HTP cannot be a clinically viable drug because of its poor pharmacokinetics. A slow-release (SR) delivery mode would be predicted to overcome the pharmacokinetic limitations of 5-HTP, substantially enhancing the pharmacological action and transforming 5-HTP into a clinically viable drug. Animal studies bear out this prediction. Thus, adjunct 5-HTP SR could be an important new treatment for TRD. Here, we review the clinical and preclinical evidence for this treatment. Trends: Clinical and preclinical evidence suggests that elevating brain 5-HTExt in a sustained fashion beyond the effect achieved by a SERT inhibitor treats TRD. Previous such drug strategies all had safety, mechanism, or pharmacokinetics limitations. Adjunctive 5-HTP strongly and synergistically augments SERT inhibitor-induced 5-HTExt -elevation, whereas 5-HTP alone has modest effects. 5-HTP has a good human safety record, but its absorption and elimination is too rapid for a 5-HTergic antidepressant. Mouse data demonstrate that adjunct 5-HTP SR safely, effectively, and in a sustained fashion elevates 5-HTExt beyond the selective serotonin reuptake inhibitor (SSRI) effect. Integrated with a large body of clinical data, these mouse data suggest that an appropriate 5-HTP SR drug would be a safe and effective therapy for TRD.